Sustainable Livelihood Strategies of the Van Gujjars in Upper Yamuna River Basin - Kasana, Sitaram (International Journal of Humanities and Education Development (IJHED), 2021)
The nomadic pastoral community of the Van Gujjars in the Upper Yamuna River Basin presents a unique case study that illustrates the intricate relationship between human livelihoods and environmental dynamics. This abstract introduces a research endeavor that seeks to explore the sustainable livelihood strategies employed by the Van Gujjars to adapt to their changing socio-economic and environmental contexts. The Van Gujjars, a nomadic pastoral community with a rich history deeply intertwined with the forests and mountains of the Upper Yamuna River Basin, have developed distinctive livelihood strategies that harmonize their traditional practices with contemporary challenges. This research aims to uncover the multifaceted ways in which the Van Gujjars sustain their livelihoods while navigating the complexities of modern development and environmental conservation.